COVID-19 and the adoption of digital marketing by micro and small enterprises in Nigeria - Omoneye Olufunke Olasanmi; Eghosa Godwin Inneh; Tajudeen John Ayoola; Lawrence Ogechukwu Obokoh; Christian Ehiobuche (Innovative Marketing, 2023)
This study aims to analyze digital marketing adoption among micro and small enterprises (MSEs) operating in Lagos State, Nigeria. This state was chosen because it was the worst hit by the COVID-19 pandemic regarding the reported number of infections and it has a large concentration of MSEs. There is no doubt that the COVID-19 pandemic brought changes to how businesses operate. It succeeded in pushing business owners into adopting new business strategies, all in the bid to adapt to the reality of the pandemic and the associated changes. The cross-sectional survey design was adopted; data were collected through an online survey of 240 MSEs operating in Lagos State. The results show no substantial increase in digital marketing adoption during the pandemic relative to the pre-pandemic era. The findings, however, reveal that digital marketing use differed significantly according to sector and size before and during the pandemic. No changes were found in digital marketing adoption in the information technology and finance sectors, while a decline in digital marketing adoption was reported in the hospitality sector. On the other hand, there was a rise in the use of digital marketing during the pandemic in the agriculture and manufacturing sectors. These findings provide an empirical managerial perspective establishing the link between reality and theoretical business underpinnings.